DESENVOLVIMENTO DE ð˜šð˜±ð˜°ð˜¥ð˜°ð˜±ð˜µð˜¦ð˜³ð˜¢ ð˜§ð˜³ð˜¶ð˜¨ð˜ªð˜±ð˜¦ð˜³ð˜¥ð˜¢ (J. E. Smith) EM GENÃ“TIPOS DE MILHO - BoiÃ§a Junior, Arlindo Leal; Santos, Terezinha Monteiro dos; Toledo, Melissa Alves de (REVISTA DE AGRICULTURA, 2020)
DESENVOLVIMENTO DE ð˜šð˜±ð˜°ð˜¥ð˜°ð˜±ð˜µð˜¦ð˜³ð˜¢ ð˜§ð˜³ð˜¶ð˜¨ð˜ªð˜±ð˜¦ð˜³ð˜¥ð˜¢ (J. E. Smith) EM GENÃ“TIPOS DE MILHO